GEMA: Google Site for Education in Mathematic and Algebra to Enhance Students’ Critical Thinking - Fatimah, Siti Lista; Rafiq Badjeber; Riska Elfira (Desimal: Jurnal Matematika, 2026)
This study addresses the persistent challenge of developing students’ critical thinking skills in mathematics, particularly in algebra, within increasingly digital learning environments. It aims to examine how a structured digital learning environment, GEMA (Google Sites for Education in Mathematics and Algebra), supports the development of students’ critical thinking processes. A quasi-experimental design with a non-equivalent control group was employed, involving an experimental group using GEMA and a control group receiving conventional instruction. Data were collected using a validated critical thinking test covering four indicators: interpretation, analysis, evaluation, and inference. The results indicate that the experimental group achieved a higher N-Gain score (0.7572, high category) compared to the control group (0.6553, medium category). Inferential analysis using an independent samples t-test revealed a statistically significant difference between groups (p = 0.044), confirming the effectiveness of the intervention. In addition, the data distribution met normality and homogeneity assumptions, supporting the validity of the statistical analysis. The most substantial improvements were observed in evaluation and inference, suggesting that the structured digital environment supports deeper reasoning processes rather than surface-level understanding. These findings indicate that the effectiveness of digital learning is not determined solely by technological features, but by the extent to which instructional design aligns with cognitive processes. In conclusion, GEMA represents an effective and pedagogically grounded approach to enhancing critical thinking in mathematics, contributing to a more nuanced understanding of how digital environments can function as cognitive mediators in supporting higher-order thinking skills.